(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Malitska L. B. Influence of ethnic stereotypes on forming personal orientation. The article deals with actual problems of ethnic identification under conditions of the possibilities of personality’s socialization, the role of ethnic identification in self-realization of personality at the modern society.